2008
DOI: 10.1158/1541-7786.mcr-07-2131
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Palifermin on Antitumor Activity of Chemotherapeutic and Biological Agents in Human Head and Neck and Colorectal Carcinoma Xenograft Models

Abstract: Damage to the gastrointestinal mucosa is a common dose-limiting toxicity of several anticancer therapies. Until recently, adequate control of oral mucositis was considered a significant unmet medical need, with most available treatments providing only palliative benefits without protecting the gastrointestinal epithelium from the damaging effects of cancer therapy. In 2005, palifermin [recombinant human keratinocyte growth factor (KGF)] was approved to decrease the incidence and duration of severe oral mucosit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 55 publications
0
22
0
Order By: Relevance
“…Five-week-old male nude mice, each weighing approximately 20 g, were divided into a xenografted positive control group ( n = 5) and xenografted experimental group ( n = 5) in which the anticarcinogenic effect of Lico-A was tested. According to the previously reported method to generate the xenograft animal model with FaDu squamous cell carcinoma (Brake et al, 2008), cells at a concentration of 1 × 10 7 cells/100 µL were injected subcutaneously into the right and left flanks of each of the control and experimental mice, respectively. After tumor formation (approximately 1,000 mm 3 ) was detected under the skin of mice that had received FaDu cell xenographs, 10 mg/kg of Lico-A dissolved in 5% ethanol and 5% ethanol without Lico-A was injected intraperitoneally into experimental and controls groups, respectively, three times per week for 8 consecutive weeks.…”
Section: Methodsmentioning
confidence: 99%
“…Five-week-old male nude mice, each weighing approximately 20 g, were divided into a xenografted positive control group ( n = 5) and xenografted experimental group ( n = 5) in which the anticarcinogenic effect of Lico-A was tested. According to the previously reported method to generate the xenograft animal model with FaDu squamous cell carcinoma (Brake et al, 2008), cells at a concentration of 1 × 10 7 cells/100 µL were injected subcutaneously into the right and left flanks of each of the control and experimental mice, respectively. After tumor formation (approximately 1,000 mm 3 ) was detected under the skin of mice that had received FaDu cell xenographs, 10 mg/kg of Lico-A dissolved in 5% ethanol and 5% ethanol without Lico-A was injected intraperitoneally into experimental and controls groups, respectively, three times per week for 8 consecutive weeks.…”
Section: Methodsmentioning
confidence: 99%
“…While there are no data to support this hypothesis, and xenograft models have demonstrated that palifermin neither stimulates tumor growth nor confers tumor protection from chemotherapy,24 it is imperative that palifermin’s inertia relative to tumor behavior be confirmed if the agent is to be widely accepted by the clinical community.…”
Section: Patient Group/populationmentioning
confidence: 99%
“…Keratinocyte growth factor-1 (KGF-1, also known as FGF-7) stimulates the growth of epithelial cells and protects those cells from chemotherapy or radiotherapy-induced oral mucositis. Recombinant KGF (Palifermin) has been approved as a cytoprotective drug to reduce the symptoms of oral mucositis [7, 8]. KGF-1 also has potential for amelioration of irradiation-induced salivary hypofunction [5, 6].…”
Section: Introductionmentioning
confidence: 99%